Persebaran Objek Wisata Dengan Sistem Informasi Geografi (SIG) Kabupaten Lampung Barat - Mentari Pratami; Rahmatullah Harianja; Wahyu Agung Sadewo (Jurusan Teknologi Produksi dan Industri, Institut Teknologi Sumatera, 2021)
The natural potential of West Lampung Regency makes it one of the tourist destinations (DTW) in Lampung Province, both foreign and domestic tourists visited to enjoy various tourist attractions in West Lampung. However, there are still many tourists, both foreign and domestic, who did not know about the tourist objects in West Lampung Regency. Therefore, it is necessary to have a mapping of tourist objects based on Geographic Information Systems (GIS) in West Lampung Regency. The research method uses descriptive research with a spatial/spatial approach. The results of the study there are 30 tourist objects which consist of natural tourism, cultural tourism and artificial tourism, 2 sub-districts that have the most tourist objects, Sumber Jaya District, which has 8 attractions and Kebun Tebu District, which has 6 attractions. This research is expected to be used as a consideration for the government in planning development in the tourism sector and serve as a medium of information about the distribution of tourism objects in West Lampung Regency.